Games, Plays and Childhood Education: notes about gender construction (Research, Society and Development, 2021)
The use of games and play in the learning process of young children is quite common in Brazil, so that pedagogical practices end up making use of these instruments to mediate the teaching process. From this, the present manuscript discusses the role of games and play in the educational practice of Early Childhood Education, as well as their contribution to the construction of development and learning about gender. To reach the objective, we opted for a bibliographic and documentary research, characterizing it as a qualitative study. We understand that Early Childhood Education contributes to the development of emotional, social and psychological processes of the child, which encompasses understanding about oneself and the other, including gender issues - here understood as a social, historical, political and cultural. As a result, we consider that games and play are perceived as activities that, in addition to producing the broad development of children, stimulate exchanges between peers, to resolve constructively conflicts, the formation of a citizen with critical and reflective sense. Along with this, we conclude that games and play make small children have a greater perception of the reality and the environment they live in, building knowledge on various subjects, including gender issues.